Micronuclei assay in oral exfoliated buccal cells of pesticides exposed agricultural labourers in Pondicherry population - A Aroumougam; A Santha Devy; A N Uma; N Vezhavendhan; S Vidyalakshmi; K R Premlal (Wolters Kluwer Medknow Publications, 2018)
Background: Occupational exposure is caused by the chemical used in pesticides that are toxic to humans and accounts for significant morbidity and mortality, especially in the developing countries. The biologically active compound present in pesticides is with various degrees of toxicity that leads to DNA damage, which, when left unattended, could lead to the process of carcinogenesis. Therefore, it is important to focus on various biometric procedures in order to evaluate the risk associated with occupational health-related issues. One among the biomonitoring test employed, the micronuclei (Mn) assay on the buccal mucosal cells is used as a part of screening in order to assess the cytotoxic status. This assay has been substantiated in the literature for the last few decades. Aims: To assess the cytotoxic damage in agricultural laborers exposed to pesticides using Mn as a biomarker. Subjects and Methods: The study involved data and sample collections from agricultural laborers (Non exposed and exposed to pesticides) by buccal smears, Papanicolaou staining and comparison of number of Mn scores as per Tolbert's and Thomas criteria, respectively. The parameters before and after exposure were analyzed by paired t-tests and partial correlation. Results: The observation of the study revealed the frequency of Mn was high in exposed individuals irrespective of age and habits when compared to that of the control group. Conclusions: In this study, as the duration of exposure increased, there was an increase in the Mn count. This indicates that there was considerable cytotoxic damage.